PERTUMBUHAN DAN HASIL TANAMAN MENTIMUN (Cucumis sativus L.) PADA BERBAGAI SISTEM OLAH TANAH DAN DOSIS PUPUK NITROGEN - Ali Muhsin; Sri Haringsih Pratiwi; Retno Tri Purnamasari (Universitas Tribhuwana Tunggadewi, 2022)
This research aimed to obtain the dose and a tillage system of nitrogen fertilizer and tillage system for optimal cucumber growth and yield. The experiment was designed in a factorial randomized block design. Treatments tested were used tillage system (P) with three levels, namely no-tillage system (P1), minimum tillage system (P2), and intensive tillage system (P3). The other factor use dose of nitrogen fertilizer (D) with three levels, namely 100 kg ha-1 (D1), 150 kg ha-1 (D2), and 200 kg ha-1 (D3) in each combination repeated three times. The results showed that the tillage system with 200 kg ha-1 dose of nitrogen significantly increased in growth and yield of cucumber plants.